Volatile compounds of roasted and steamed Malaysian tropical almond nut (Terminalia catappa L.) - Lasekan, Ola; Khatib, Alfi; Abbas, Kassim A. (Taylor and Francis, 2012)
The flavor extract components contributing to the characteristic aroma notes of roasted and steamed tropical almond nuts were investigated by means of gas chromatographyolfactometry and mass spectrometry of solvent extracts. Roasting and steaming data revealed all of the main classes of compounds commonly listed as thermally generated flavors in oily seeds. A total of 72 volatile compounds were identified in the sample from roasted nuts; among these were 27 hydrocarbons, 12 aldehydes, 12 ketones, 8 acids, 4 esters, 3 alcohols, 3 furans, and a pyrazine. The steamed nuts, however, yielded 66 peaks from which 63 volatile compounds were identified (22 hydrocarbons, 9 aldehydes, 9 ketones, 9 esters, 4 acids, 9 alcohols, and a pyrazine). The small number of aldehydes, ketones, pyrazine, and alcohols identified are the ones most likely to contribute to the aroma of the nuts.